2013
DOI: 10.1111/mms.12042
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral impacts of disentanglement of a right whale under sedation and the energetic cost of entanglement

Abstract: DRAFT -DO NOT CITE OR CIRCULATE. Page 2 2 Abstract 22 23Protracted entanglement in fishing gear often leads to emaciation through reduced 24 mobility and foraging ability, and energy budget depletion from the added drag of towing 25 gear for months or years. We examined changes in kinematics of a tagged entangled 26North Atlantic right whale (Eg 3911), before, during and after disentanglement on 15 Jan 27 2011. To calculate the additional drag forces and energetic demand associated with 28 various gear configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 46 publications
4
72
0
Order By: Relevance
“…Further, the additional drag from trailing fishing gear can exacerbate energy expenditure and prevent efficient foraging. Van der Hoop et al (2013) placed a Dtag on an entangled Northern right whale and found slower diving ascents and descents, as well as shallower dives during entanglement than for whales that were not entangled [18]. Modeling the drag force of gear attached to the entangled right whale also showed that whales entangled in fishing gear experience a greater energetic demand [18].…”
Section: Group Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the additional drag from trailing fishing gear can exacerbate energy expenditure and prevent efficient foraging. Van der Hoop et al (2013) placed a Dtag on an entangled Northern right whale and found slower diving ascents and descents, as well as shallower dives during entanglement than for whales that were not entangled [18]. Modeling the drag force of gear attached to the entangled right whale also showed that whales entangled in fishing gear experience a greater energetic demand [18].…”
Section: Group Compositionmentioning
confidence: 99%
“…Van der Hoop et al (2013) placed a Dtag on an entangled Northern right whale and found slower diving ascents and descents, as well as shallower dives during entanglement than for whales that were not entangled [18]. Modeling the drag force of gear attached to the entangled right whale also showed that whales entangled in fishing gear experience a greater energetic demand [18]. Further, there appears to be a critical duration period in which the duration of additional drag due to entanglement can be a predictor of survival [19].…”
Section: Group Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ultrasonic measurements showed increased blubber thickness in older juveniles (8 yr) compared to younger juveniles (1 to 2 yr) (Miller et al 2011). Anthropogenic impacts, including entanglement in fishing gear, may impede foraging ability, increase energy draw due to disruption of the hydrostatic oral seal (Lambertsen et al 2005, Cassoff et al 2011, or increase drag forces created by the entangling gear , Cassoff et al 2011, van der Hoop et al 2014. Although each of these factors creates energetic demands, the degree to which they alter body condition as well as the speed at which changes can be visually detected have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The North Atlantic right whale Eubalaena glacialis remains one of the most endangered large whales in the world, despite a myriad of agency and institutional recovery efforts (van der Hoop et al 2013). High levels of anthropogenic-related mortality as well as variable annual reproductive rates in E. glacialis have led to population growth that is lower (~2.6%) than their southern right whale E. australis counterparts (~7.5%) and other large baleen whale species in the western North Atlantic (Best et al 2001, Waring et al 2015.…”
Section: Introductionmentioning
confidence: 99%